Stava naslonk v stari cerkveni slovanščini - Kuntner, Rok (Jezik in slovstvo, 2025)
The article examines the placement of clitics in Old Church Slavonic canonical texts in relation to the reconstructed Proto-Indo-European linguistic state. It complements existing findings with a case study on the placement of clitics in the Gospel text of the Codex Marianus, one of the oldest and linguistically most archaic Old Church Slavonic monuments. The study demonstrates that the placement of clitics in Old Church Slavonic was generally governed by two principles: (1) the etymological principle, according to which clitics of Proto-Indo-European origin are positioned after the first stressed word in a sentence, while younger clitics are placed postverbally; and (2) the syntactic principle, according to which, in negative and interrogative main clauses as well as in subordinate clauses, clitics – regardless of their age – are positioned immediately after the negation, question word, or conjunction. These principles represent tendencies and do not exclude individual deviations, which can be explained by analogy or the influence of the word order in the Greek Vorlage. By uncovering the interplay of synchronic and diachronic factors influencing clitic placement in the Old Church Slavonic linguistic system, the article provides a basis for further research that would encompass the entire Old Church Slavonic canon. It also opens the door for discussions on the diachronic interpretation of clitic placement in Old Church Slavonic within the broader Slavic and Indo-European context.
Keywords: besedni red; clitics; naslonke; Old Church Slavonic; skladnja; stara cerkvena slovanščina; syntax; Wackernagel‘s Law; Wackernaglovo pravilo; word order